Determinants of G quadruplex‐induced epigenetic instability in REV1‐deficient cells. (4th September 2014) - Schiavone, Davide; Guilbaud, Guillaume; Murat, Pierre; Papadopoulou, Charikleia; Sarkies, Peter; Prioleau, Marie‐Noëlle; Balasubramanian, Shankar; Sale, Julian E
Abstract REV1‐deficient chicken DT40 cells are compromised in replicating G quadruplex (G4)‐forming DNA. This results in localised, stochastic loss of parental chromatin marks and changes in gene expression. We previously proposed that this epigenetic instability arises from G4‐induced replication fork stalls disrupting the accurate propagation of chromatin structure through replication. Here, we test this model by showing that a single G4 motif is responsible for the epigenetic instability of the BU‐1 locus in REV1‐deficient cells, despite its location 3.5 kb from the transcription start site (TSS). The effect of the G4 is dependent on it residing on the leading strand template, but is independent of its in vitro thermal stability. Moving the motif to more than 4 kb from the TSS stabilises expression of the gene. However, loss of histone modifications (H3K4me3 and H3K9/14ac) around the transcription start site correlates with the position of the G4 motif, expression being lost only when the promoter is affected. This supports the idea that processive replication is required to maintain the histone modification pattern and full transcription of this model locus.